2006
DOI: 10.1038/sj.bmt.1705475
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antioxidants in subjects before hematopoietic stem cell transplantation

Abstract: Chemo-irradiation induced oxidative damage to vascular endothelium may contribute to pulmonary complications of hematopoietic stem cell transplantation (HSCT). We measured antioxidants, markers of oxidative stress and plasma antioxidant capacity in plasma or serum from 24 subjects at day 7 before HSCT and 20 control subjects. The plasma concentration of extracellular glutathione peroxidase (GPX-3) was significantly reduced in the HSCT subjects compared with controls (HSCT: 98742 lg/ml, control: 169756 lg/ml, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…HSCT patients were previously shown to be under chronic oxidative stress [1,12]. Oxidative stress was associated with high-dose chemotherapy and/or radiotherapy in subjects undergoing HSCT [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSCT patients were previously shown to be under chronic oxidative stress [1,12]. Oxidative stress was associated with high-dose chemotherapy and/or radiotherapy in subjects undergoing HSCT [13].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy and radiation therapy are associated with increased formation of free radicals. Reactive oxygen species (ROS) have the ability, either directly or indirectly, to damage all biomolecules, including proteins, lipids, DNA, and carbohydrates [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E is an antioxidant agent that neutralizes peroxides and oxygen radicals, prevents the lipid breakdown reaction chain, and protects against oxidative damage by settling on cell and organelle membranes [12,27]. The drugs used in chemotherapy are thought to exhibit cytotoxic effects by establishing oxidative stress [5,6,7]. In theory, therefore, antioxidants are thought to reduce the side-effects of these agents by scavenging free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical trials [4] and experimental studies [5] for the prevention of infertility resulting from chemotherapy have been carried out; research suggests that oxidative stress that rises with chemotherapy is a factor leading to infertility [5]. In addition, increased oxidative stress and decreased levels of antioxidants were reported in patients received chemotherapy [6,7]. Borekci et al [5] also determined an increase in the levels of malondialdehyde (MDA), a product of lipid peroxidation, and a decrease in levels of total glutathione (tGSH), an endogenous antioxidant, in ovarian tissue of rats receiving cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that subjects before HSCT have lower plasma concentrations of glutathione peroxidase, an important component of the circulating antioxidant system, compared with controls. 24 Thus, increased reactive oxygen species production along with an impaired antioxidant system may contribute to muscle weakness in the post-HSCT period.…”
Section: Discussionmentioning
confidence: 99%